2019
DOI: 10.1111/1751-7915.13378
|View full text |Cite
|
Sign up to set email alerts
|

Omnipresent Maxwell's demons orchestrate information management in living cells

Abstract: Summary The development of synthetic biology calls for accurate understanding of the critical functions that allow construction and operation of a living cell. Besides coding for ubiquitous structures, minimal genomes encode a wealth of functions that dissipate energy in an unanticipated way. Analysis of these functions shows that they are meant to manage information under conditions when discrimination of substrates in a noisy background is preferred over a simple recognition process. We show here … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 224 publications
(237 reference statements)
2
27
0
Order By: Relevance
“…They often need to be further stabilized chemically. Besides agents that use energy to discriminate among the many RNA‐folded structure and retain only those that are properly shaped (Tamaru et al , 2018; Boel et al , 2019), ribosomal RNAs are modified, in general via the action of AdoMet‐dependent RNA methylases (Sergiev et al , 2018). A few ribosomal proteins (many more in Eukarya than in Bacteria or Archaea) are also modified by such methylases, but these modifications appear to have less essential functions.…”
Section: Adomet‐dependent Methylations Of the Translation Machinerymentioning
confidence: 99%
See 2 more Smart Citations
“…They often need to be further stabilized chemically. Besides agents that use energy to discriminate among the many RNA‐folded structure and retain only those that are properly shaped (Tamaru et al , 2018; Boel et al , 2019), ribosomal RNAs are modified, in general via the action of AdoMet‐dependent RNA methylases (Sergiev et al , 2018). A few ribosomal proteins (many more in Eukarya than in Bacteria or Archaea) are also modified by such methylases, but these modifications appear to have less essential functions.…”
Section: Adomet‐dependent Methylations Of the Translation Machinerymentioning
confidence: 99%
“…When alone, RimO has a reversible action. However, in concert with ATP‐dependent factor RimOB (YcaO), the reaction becomes irreversible (Sikandar et al , 2019), witnessing yet another example of a protein that acts as a Maxwell's demon [see Sherrington (1940) p. 78 for an ‘animist’ attempt to use the concept as a physicochemical metaphor of the cell's life] needed to discriminate the relevant peptide against similar ones, while asking for compulsory energy dissipation to be reset to their original state (Boel et al , 2019).…”
Section: Adomet‐dependent Methylations Of the Translation Machinerymentioning
confidence: 99%
See 1 more Smart Citation
“…In order to illustrate this problem it is useful to analyze how Nature deals with it in living organisms. The requisite for success of an enzyme in current cells, for instance, is not to establish correct interaction with the substrate, but rather to discriminate between similar substrates and exclude those that do not lead to a transformation process that is useful (functional) to the cell [23]. Supramolecular chemistry has extensively shown that recognition alone is efficient in the absence of noise, i.e., of similar competitive structures [24].…”
Section: Introduction: Stating the Problemmentioning
confidence: 99%
“…The ratchet-like discriminative process allows information to accumulate, which the system uses not only to build its own components but also to “know” how and when they must be built. Some researchers have proposed that biological molecular machines (e.g., transmembrane transporters and ribosomes) actually behave as a material implementation of Maxwell demons [27], as information-managing entities at the expense of ATP hydrolysis [23,25]. Energy dissipation in this context is the price to pay for maintaining organizational closure in living organisms, as it allows information management to ensure the constitutive cell processes are well above the constraints of noise.…”
Section: Introduction: Stating the Problemmentioning
confidence: 99%